Determinants of early-life lung function in African infants. Issue 5 (17th November 2016) - Gray, Diane; Willemse, Lauren; Visagie, Ane; Czövek, Dorottya; Nduru, Polite; Vanker, Aneesa; Stein, Dan J; Koen, Nastassja; Sly, Peter D; Hantos, Zoltán; Hall, Graham L; Zar, Heather J
Abstract : Background: Low lung function in early life is associated with later respiratory illness. There is limited data on lung function in African infants despite a high prevalence of respiratory disease. Aim: To assess the determinants of early lung function in African infants. Method: Infants enrolled in a South African birth cohort, the Drakenstein child health study, had lung function measured at 6–10 weeks of age. Measurements, made with the infant breathing via a facemask during natural sleep, included tidal breathing, sulfur hexafluoride multiple breath washout and the forced oscillation technique. Information on antenatal and early postnatal exposures was collected using questionnaires and urine cotinine. Household benzene exposure was measured antenatally. Results: Successful tests were obtained in 645/675 (95%) infants, median (IQR) age of 51 (46–58) days. Infant size, age and male gender were associated with larger tidal volume. Infants whose mothers smoked had lower tidal volumes (−1.6 mL (95% CI −3.0 to −0.1), p=0.04) and higher lung clearance index (0.1 turnovers (95% CI 0.01 to 0.3), p=0.03) compared with infants unexposed to tobacco smoke. Infants exposed to alcohol in utero or household benzene had lower time to peak tidal expiratory flow over total expiratory time ratios, 10% (95% CI −15.4% to −3.7%), p=0.002) and 3.0% (95% CI −5.2% to −0.7%, p=0.01) lower respectively compared with unexposed infants. HIV-exposed infants had higher tidal volumes (1.7 mL (95% CI 0.06 to 3.3) p=0.04) compared with infants whose mothers were HIV negative. Conclusion: We identified several factors including infant size, sex, maternal smoking, maternal alcohol, maternal HIV and household benzene associated with altered early lung function, many of which are factors amenable to public health interventions. Long-term study of lung function and respiratory disease in these children is a priority to develop strategies to strengthen child health.